THE CHARTER AND BY-LAWS OF THE CITY OF MERIDEN 135 (1875) - (:unkn) unknown (General Publisher, 1869)
Prohibited the discharge of any pistol, gun, cannon, or other fire-arm with the limits of the city. Violators forfeit the weapon and fined five dollars.
--
Keywords: DISCHARGE